2021
DOI: 10.3390/ijms23010174
|View full text |Cite
|
Sign up to set email alerts
|

Aging Impairs Reverse Remodeling and Recovery of Ventricular Function after Isoproterenol-Induced Cardiomyopathy

Abstract: Information about heart failure with reduced ejection fraction (HFrEF) in women and the potential effects of aging in the female heart is scarce. We investigated the vulnerability to develop HFrEF in female elderly mice compared to young animals, as well as potential differences in reverse remodeling. First, HF was induced by isoproterenol infusion (30 mg/kg/day, 28 days) in young (10-week-old) and elderly (22-month-old) female mice. In a second set of animals, mice underwent isoproterenol infusion followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The aged heart undergoes a series of changes at the molecular level that leave it vulnerable to myocardial injury in cardiovascular diseases such as myocardial infarction and cardiomyopathy ( 22 , 23 ). In our study, we found that the expression of SP1, which is a transcription factor that is upstream of Cirbp , was decreased in aged donor hearts, leading to the attenuation of hypothermic cardioprotection.…”
Section: Discussionmentioning
confidence: 99%
“…The aged heart undergoes a series of changes at the molecular level that leave it vulnerable to myocardial injury in cardiovascular diseases such as myocardial infarction and cardiomyopathy ( 22 , 23 ). In our study, we found that the expression of SP1, which is a transcription factor that is upstream of Cirbp , was decreased in aged donor hearts, leading to the attenuation of hypothermic cardioprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Park et al found that patients with HFiEF were younger than those without ( 18 ). Furthermore, animal experiments suggested that aging animals showed persistent tissue fibrosis and cardiac dysfunction with impaired reverse remodeling, unlike younger animals that experienced complete cardiac function recovery ( 19 ). Older HF patients carry a higher risk of comorbidities such as diabetes mellitus, hypertension, and anemia, and are prone to significant calcification and multiple and diffuse lesions ( 11 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we explored whether β-ecdysterone treatment affects the sympathetic central nervous system. We applied resting-state functional magnetic resonance imaging (rs-fMRI) to achieve real-time and non-invasive detection of whole brain activity [62][63][64] . Animal studies using rs-fMRI are often applied to nervous system diseases.…”
Section: Interdisplinary Investigation Of Central-peripheral Cardiova...mentioning
confidence: 99%